2016
DOI: 10.1002/jib.368
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of quality and production process of a non‐alcoholic stout beer using reverse osmosis

Abstract: The market for low‐alcohol and non‐alcoholic beer has been increasing owing to factors such as health concerns, calorie content, strict traffic laws and religion, among others. Beer presents some good nutritional characteristics such as B‐complex vitamins, antioxidants, minerals, fibre, protein and carbohydrates. The availability of non‐alcoholic products is still very low in Brazil and worldwide. This study produced four samples of non‐alcoholic dark beer derived from a Foreign Extra Stout beer style with 6.6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 24 publications
(41 reference statements)
1
12
2
Order By: Relevance
“…Physical processing can include thermal processes, such as rectification or thin film evaporation, whereas membrane processes can include dialysis, osmotic distillation, pervaporation, nanofiltration (NF) and reverse osmosis (RO) ( Blanco et al, 2016 , Branyik et al, 2012 , Güzel et al, 2020 ). In a comprehensive review on NAB production, Branyik et al (2012) found that all techniques produced significant losses in volatiles, however RO seemed to show the smallest change, with further encouraging results found from other researchers when dealcoholizing beer, wine and cider ( Alcantara et al, 2016 , Catarino et al, 2007 , Catarino, 2010 , Gil et al, 2013 , Lopez et al, 2002 , Pilipovik and Riverol, 2005 ).…”
Section: Introductionmentioning
confidence: 71%
“…Physical processing can include thermal processes, such as rectification or thin film evaporation, whereas membrane processes can include dialysis, osmotic distillation, pervaporation, nanofiltration (NF) and reverse osmosis (RO) ( Blanco et al, 2016 , Branyik et al, 2012 , Güzel et al, 2020 ). In a comprehensive review on NAB production, Branyik et al (2012) found that all techniques produced significant losses in volatiles, however RO seemed to show the smallest change, with further encouraging results found from other researchers when dealcoholizing beer, wine and cider ( Alcantara et al, 2016 , Catarino et al, 2007 , Catarino, 2010 , Gil et al, 2013 , Lopez et al, 2002 , Pilipovik and Riverol, 2005 ).…”
Section: Introductionmentioning
confidence: 71%
“…Variations in heat during cooking, mashing, malting and other stages of the process resulting in the low quality of brewed beer . For example, a low‐temperature step leads to a longer complete conversion time for sugars, producing a highly attenuated beer with high alcohol content but less body and mouth‐feel.…”
Section: Resultsmentioning
confidence: 99%
“…The producers of beer are keen to brew a product that is acceptable to consumers. A major challenge for the brewing industry is to develop low‐alcohol and long‐shelf‐life beers with acceptable organoleptic characteristics, since the fermentation process is by uncontrolled inoculation and chance contamination under non‐standard hygienic conditions . It was noted that in developing countries, fermented foods/drinks are produced under uncontrolled conditions using traditional habits and age‐old techniques .…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, non-alcoholic beer of good quality has been produced by reverse osmosis with a hydrophilic membrane. Alcantara et al (22) report that membrane processing has advantages for alcoholic beverages, as both the temperature and pressure are controlled. In addition to reverse osmosis, cross flow microfiltration and pervaporation have also been applied.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to reverse osmosis, cross flow microfiltration and pervaporation have also been applied. Cross flow microfiltration involves the passage of a fluid through a porous membrane, which promotes clarification by retention of suspended solids with pressure difference as the driving force . Pervaporation, on the other hand, is the selective permeation of species through a non‐porous membrane followed by evaporation at the permeate side.…”
Section: Introductionmentioning
confidence: 99%